Patterns and Correlates of Supply Chain Trade in MENA and SSA - Jaime de Melo; Jean-Marc Solleder (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
Strong participation in Global Supply Chains (GSCs) (aka Global Value Chains (GVCs)) is an indication of the structural transformation at the heart of the 'Africa we want' described in African Union's Agenda 2063 project. We discuss challenges at measuring GSCs and report new input- output based measures (upstreamness and downstreamness of exports) at several levels: across countries, regions, and sectors over the period 1995-2015. We also report participation measures based on firm-level data and new estimates of factors affecting participation of sectors in GVCs over the period 1995-2015. On average, for both Africa and MENA, exports have a low content of imported intermediates and exports undergo further transformation in destination countries before reaching consumers. Compared with other regions, both Africa and MENA mostly engage in supply chain trade with countries outside their respective region. Firm-level estimates for several countries show that African firms are scarcely engaged in supply chain trade. In sum, in spite of regional trade agreements focussing on reducing trade barriers to intra-regional trade, regional value chains have failed to develop in both regions. [...]
Keywords: 330